College algebra - Stewart, James; Redlin, Lothar; Watson, Saleem (USA : Cengage, 2024)
"Do your students attempt to memorize facts and mimic examples to make it through algebra? Instead, provide students with a solid foundation in the principles of mathematical thinking with COLLEGE ALGEBRA, 8th Edition by best-selling author team Stewart/Redlin/Watson. This popular, updated edition explains concepts simply and clearly, overcoming learning barriers without avoiding difficult points. New and revised applications, new content and updated review opportunities provide a solid understanding of the principles behind algebra. A focus on modeling emphasizes the relevance of what students are learning while new Discovery Projects demonstrate how concepts apply. Comprehensive and evenly paced, this updated edition provides an attention to detail and clarity that sets this author team apart. Accompanying WebAssign digital resources further reinforce true student comprehension."
Includes index.
Keywords: Algebra; Algebra -- Textbooks